Experimental Determination of Pressure Fluctuations in Stilling Basin with Sudden Expanding and Roughened Bed - Marzieh Naemhasani; Kouros Nekoufar; Morteza Biglarian; Morteza Jamshidi (محیط زیست و مهندسی آب, 2022)
The effect of fluctuating pressures due to turbulence on the hydraulic jump causes significant damage to the relaxation pool. Moreover, the presence of roughness in the bed changes the behavior of flow lines and the formation of vortices during the jump. Therefore, the aim of this study was to determine the effect of the presence of roughness on hydrodynamic pressures in type S hydraulic jump in sudden divergence sections. For this purpose, experiments were performed in a relatively large channel with a width of 0.8 and a length of 12 m in the calm pool with divergence ratios of 0.33, 0.5, 0.67 and 1 in the range of Frued numbers between 2 to 9.5. Roughness elements with a height of 3 cm and specified distances were placed in the channel bed and downstream of the divergence section. In order to determine the effects of roughness on the level of hydrodynamic pressures, the experiments were performed in two separate stages, including a completely flat pool bed without the presence of roughness in the first stage (77 experiments) and with the presence of roughness in the pool floor in the second stage (81 experiments). The results showed that the presence of roughness in the bed reduces the intensity of pressure fluctuations in the relaxation pool. In addition, in sudden divergent sections, due to the formation of lateral vortices, the energy drop increases and the intensity of pressure fluctuations decreases. The maximum reduction rates of pressure fluctuations were estimated to be 27, 46 and 58% for the divergence ratios of 0.67, 0.5 and 0.33 in the rough bed, respectively.